Generation of one- DOF epicyclic gear trains with up to eight links. (2021) - Mustafa, Jiyaul; Hasan, Ali
Abstract: The generation of epicyclic gear trains (EGTs) by application of graph theory has a major focus by researchers to avoid duplicity of mechanisms as well as topological structural and synthesis analysis. This paper presents the generation of EGTs with one degree of freedom up to eight links. The method has been formulated on the basis of conventional graphs, the graphs converted into adjacency matrices and then, obtained wiener number for structural synthesis and isomorphic property. The results obtained by this method have been fully satisfied with references